An Empirical Analysis of Monetary Approach to Balance of Payments in Nepal - Ghimire, Bachchu Ram; Paudel, Mandira (International Research Journal of MMC, 2025)
This study aims to identify the economic variables that have significant impact on the Balance of Payments position in Nepal. This research further studies the applicability of the Monetary Approach to Balance of Payments (MABP) in Nepal. Time series data over the period from 1980 A.D. to 2024 A.D. has been considered in this research. The secondary data for the study has been obtained from various publications of Nepal Rastra Bank. Net Foreign Assets (NFA) has been taken as the dependent variable, as a proxy for Balance of Payments, whereas Nominal GDP, Consumer Price Index, Exchange Rate, Net Domestic Assets and Money Multiplier are taken as the independent variables. Ordinary Least Squares method has been used for data analysis by modelling a multiple regression equation. Similarly, descriptive statistics including Mean and Standard Deviation have been calculated for the variables followed by correlation and regression analysis. Augmented Dickey Fuller test was performed to ensure the stationarity of the time series data used in the model. From the regression analysis, Consumer Price Index, Net Domestic Assets and Money Multiplier were concluded to be statistically significant for determining BOP position in Nepal. Consumer Price Index has a statistically positive relationship with Net Foreign Assets, whereas Net Domestic Assets and Money Multiplier have a statistically negative relationship with Net Foreign Assets. On the contrary, Nominal GDP and Exchange Rate were found to be statistically insignificant in addressing BOP disequilibrium in the country. Hence, MABP model is still found to be relevant in the context of Nepal and monetary variables play effective role in maintaining BOP stability in Nepalese economy. This study will be helpful for the future research works on the MABP model and provide necessary recommendations to the concerned authorities including the central bank (NRB) and the government authorities.